Transnational Chicanx perspectives on Ana Castillo - Hernández, Bernadine Marie; Roybal, Karen R. (Latinx and Latin American profiles., 2021)
Transnational Chicanx Perspectives on Ana Castillo is the first edited collection that focuses on Castillo's oeuvre, which directly confronts what happens in response to cultural displacement, mixing, and border crossing. Divided into five sections, this collection thinks about Castillo's poetics, language, and form, as well as thematic issues such as borders, immigration, gender, sexuality, and transnational feminism.